Opioid-Based vs opioid-free anesthesia in breast cancer surgery - Shraddha Naik; Avinash Bhosale; Dhanashree Kale; Pradeep B Patil (Journal of Pharmacy and Bioallied Sciences, 2023)
Introduction: Breast cancer is the most widely recognized malignant growth in ladies in India and accounts for 14% of all tumors in women. Modified radical mastectomy (MRM) is a surgery done for breast cancer. It leads to about 30% chances of postoperative nausea and vomiting (PONV) and 40% pain in the immediate postoperative period. Objectives: Changes in blood pressure after intubation, waiting time for postoperative pain medication, and possibility of adverse effects. Methodology: After the approval of ethical committee, the study was conducted in the procedure and possible complications associated with the procedure were explained to patients. Written informed consent was obtained from each patient. Result and Conclusion: We conclude that opioid-free anesthesia is “more effective in reducing the incidence of postoperative nausea and vomiting, produces stable hemodynamics, and reduces incidence of side effects when compared with opioid-based general anesthesia in patients undergoing breast cancer surgeries.”